Evidence for Mediating Role of Affective Commitment on Green Human Resource Management and Organisational Citizenship Behaviour - Manita Kusi,; Fuqiang Zhao,; Maroy Prisca Rasoanirina, (Asian Academy of Management Journal, 2021)
Exploring management fields in terms of green policies is essential to create a footprint on today’s global corporate world; it is very important for all staff, employers, stakeholders, and other customers. This work attempts to study the relationship between the management of green human resources and the actions of organisational citizenship with the mediating role of affective commitment. The analysis relied on the emerging theory of abilitymotivation- opportunity (AMO) to use all the green human resource management (GHRM) attributes. Well renowned secondary school of Kathmandu Valley staff participated in the data collection. Three hundred and fifty fully-filled questionnaires were returned through a self-structured sampling tool. Staff having academic qualifications of at least graduate degrees were preferred for better understanding and effective data quality. A widely used PLS-SEM method was applied to analyse small sample-sized studies and ensures the normal distribution of data. The research highlights the GHRM method and its effect on the engagement of workers to their actions in the organisation. In addition, concerning GHRM and organisational citizenship behaviour (OCB), affective commitment (AC) has formed a mediating role. Only secondary schools are included in the study; the outcome is a fruitful review of the effects of GHRM implementation in the education sector. Numerous studies have reconnoitered various variables to link the GHRM with the organisational studies. The complementary partial mediation effect of AC to OCB is an attempt of showing novelty in the field of education sector in the study. The study suggests a globalised study regarding GHRM for future endeavours.